Three‐Component Synthesis of Indanone‐Fused Spirooxindole Derivatives. Issue 21 (10th June 2013) - Chen, Xue‐Bing; Liu, Xi‐Ming; Huang, Rong; Yan, Sheng‐Jiao; Lin, Jun
Abstract: A simple, straightforward and versatile multicomponent protocol for the synthesis of indanone‐fused spirooxindole derivatives has been developed. The strategy involves the one‐pot three‐component reaction of heterocyclic ketene aminals, 1 H ‐indene‐1, 3(2 H )‐dione and the dicarbonyl compounds isatins or acenaphthenequinone in an ethanol/water medium catalysed by p ‐TSA at reflux. Mild reaction conditions, operational simplicity, wide substrate scope and overall excellent yields make this method highly efficient for the library synthesis of indanone‐fused spirooxindole. Abstract : A simple, straightforward and versatile multicomponent protocol for the synthesis of indanone‐fused spirooxindole derivatives has been developed. The strategy involves the one‐pot three‐component reaction of heterocyclic ketene aminals, 1 H ‐indene‐1, 3(2 H )‐dione and the dicarbonyl compounds isatins or acenaphthenequinone in an ethanol/water medium catalysed by p ‐TSA at reflux.